FUNCTIONAL DIFFERENCES OF GRADUONYMY IN ACTIVE VERBS OF ENGLISH AND UZBEK (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article will discuss the problems arousing in the process of differentiating graduonymy in active verbs which are encountered by many scholars during their research.